Knowledge and Attitude towards Sexually Transmitted Disease and HIV/AIDS among Secondary Level School Students - Sunuwar, Urmila (KMC Research Journal, 2019)
Adolescent sexuality leads to adolescent pregnancy, unsafe abortion, reproductive tract infections, sexually transmitted infections and HIV/AIDS.The study objective is to assess the knowledge and attitude towards sexually transmitted disease and HIV/AIDs among secondary level school students of Kathmandu metropolitan city. Descriptive cross-sectional study was conducted by using self-administered questionnaires. The study population was school adolescent students. They were selected by using random sampling method. After data collection, descriptive statistics were used to analyse the collected data. Knowledge and attitude towards sexual transmitted disease is significantly varied with student’s background characteristics. Around 95% of study population had heard about sexually transmitted disease and almost 99% heard about HIV/AIDS. Majority 85.6% of students reported that they “agreed” that HIV/AIDS is a major problem in Nepal however 14.4% students were not agreed on it. 73% respondents reported that teachers are the main source of knowledge regarding sexual transmitted disease and HIV/AIDS.It is clear that students need a specific package of education about sexual and reproductive health in school curriculum so that they could gain more information about sexually transmitted disease and HIV/AIDS.